PERTANGGUNGJAWABAN HUKUM TERHADAP PEJABAT TATA USAHA NEGARA DALAM MENGELUARKAN KEPUTUSAN TATA USAHA NEGARA - Putri Marsita (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractState Administration Officials in issuing a State Administration Decree are often negligent or contrary to a sense of justice so as to make the community / individual / legal entity feel uneasy about the State Administration Decree issued by the State Administration Officer, so this often creates legal conflicts . Administrative Law No. 30 of 2014 concerning Government Administration philosophically encourages the birth of a system of government administration that serves the public in an efficient, transparent and accountable manner. During this time, public officials who spearhead the administration of the government still have a paradigm as an elite group that is served not serving the community, so that sometimes a decision of the State Administration Officer is considered contrary to a sense of justice for the community / individual / legal entity. The method used in research This method uses normative juridical research. Based on the results of research, related to the actions or actions of the State Administration Officer in issuing a decision that becomes a conflict or dispute is an act that is contrary to the General Principles of Good Governance which in these principles uphold the norms of decency, propriety, and legal norms , to realize a state that is clean and free of corruption, collusion and nepotism.